2008
DOI: 10.1098/rsta.2008.0170
|View full text |Cite
|
Sign up to set email alerts
|

The black hole symphony: probing new physics using gravitational waves

Abstract: The next decade will very likely see the birth of a new field of astronomy as we become able to directly detect gravitational waves (GWs) for the first time. The existence of GWs is one of the key predictions of Einstein's theory of general relativity, but they have eluded direct detection for the last century. This will change thanks to a new generation of laser interferometers that are already in operation or which are planned for the near future. GW observations will allow us to probe some of the most exoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In this section we discuss the potential of space-based low-frequency GW detectors to probe the structure of massive compact objects and the possible interpretation of these results. Short reviews of the prospects for testing relativity with measurements of black-hole "hair" can be found in [73,191].…”
Section: Tests Of the Nature And Structure Of Black Holesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we discuss the potential of space-based low-frequency GW detectors to probe the structure of massive compact objects and the possible interpretation of these results. Short reviews of the prospects for testing relativity with measurements of black-hole "hair" can be found in [73,191].…”
Section: Tests Of the Nature And Structure Of Black Holesmentioning
confidence: 99%
“…Therefore it is reasonable to design an approach to spacetime mapping that looks for inspirals into Kerr black holes and quantifies any deviations from such inspirals that may be present. One such approach to spacetime mapping was described in [191]. The starting point is to assume that GR is correct, and that the source's spacetime is vacuum and axisymmetric.…”
Section: Interpretation Of Observationsmentioning
confidence: 99%
“…The overall waveform is modulated by precession of the orbital plane with respect to the line of sight to the observer. Figure taken from [20], adapted from [119]. inspiral at any given time.…”
Section: Astrophysical Impactmentioning
confidence: 99%
“…The slow evolution of EM-RIs means that a large number of cycles can be observed during the inspiral, which will provide constraints on the parameters of the source with remarkable precision [12,13]. Previous work has indicated that LISA will be able to place constraints on the dimensionless Kerr spin parameter, a, of the primary black hole in an EMRI, at the level of 1 part in 10 4 for moderately spinning, a ∼ 0.9, primaries [3,4,14,15]. In this paper, we explore how well LISA will be able to measure the spin parameter for very rapidly rotating black holes, i.e., systems in which the spin parameter is close to the maximum value allowed by general relativity.…”
Section: Introductionmentioning
confidence: 99%